2016
DOI: 10.1101/cshperspect.a018853
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis in the Developing and Adult Brain—Similarities and Key Differences

Abstract: Adult neurogenesis in the mammalian brain is often viewed as a continuation of neurogenesis at earlier, developmental stages. Here, we will critically review the extent to which this is the case highlighting similarities as well as key differences. Although many transcriptional regulators are shared in neurogenesis at embryonic and adult stages, recent findings on the molecular mechanisms by which these neuronal fate determinants control fate acquisition and maintenance have revealed profound differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 175 publications
(282 reference statements)
1
86
0
3
Order By: Relevance
“…Postnatally, the population of hippocampal progenitors becomes restricted to the subgranular zone of the DG and transforms into adult neural stem cells that continue to divide, although at a much lower rate than in embryos. Adult neurogenesis is not simply an extension of a developmental process into the adulthood because the environment in the postnatal brain is not more neurogenic , implying that other mechanisms may be involved in the postnatal regulation of granule cell generation. However, in the adult hippocampus, Wnt/β‐catenin signaling is still active, both in the SGZ and DG, which has been demonstrated in Wnt reporter mice .…”
Section: Neurogenesis In the Hippocampusmentioning
confidence: 99%
“…Postnatally, the population of hippocampal progenitors becomes restricted to the subgranular zone of the DG and transforms into adult neural stem cells that continue to divide, although at a much lower rate than in embryos. Adult neurogenesis is not simply an extension of a developmental process into the adulthood because the environment in the postnatal brain is not more neurogenic , implying that other mechanisms may be involved in the postnatal regulation of granule cell generation. However, in the adult hippocampus, Wnt/β‐catenin signaling is still active, both in the SGZ and DG, which has been demonstrated in Wnt reporter mice .…”
Section: Neurogenesis In the Hippocampusmentioning
confidence: 99%
“…One notable example is that all these cells commonly express glial fibrillary acidic protein (Gfap) and the glial high affinity glutamate transporter (Slc1a3 or Glast) (Beckervordersandforth et al, 2010;Doetsch et al, 1999). Recent studies have also revealed many common molecular players and mechanisms that control the maintenance and differentiation of NSCs in both regions (see Götz et al (2016) and references therein). For example, in both the VZ-SVZ and SGZ, the Sox family of high-mobility-group-containing transcription F I G U R E 2 Stepwise differentiation of neural stem cells (NSCs) into new neurons through intermediate cell types in the postnatal and adult brain.…”
Section: Similarities and Differences Between Neurogenesis And Nscsmentioning
confidence: 99%
“…Abbreviations: aNSCs, activated neural stem cells; NB, neuroblast; qNSCs, quiescent neural stem cells; TAP, transient amplifying progenitor. Others are the same as Figure 1 factors (TFs) Sox2 and Sox9, as well as the orphan nuclear receptor Tlx (Nr2e1) have been shown to be crucial for the longterm maintenance of adult NSCs, whereas the basic helix-loop-helix TF Ascl1, the homeodomain factor Prox1, and Sox family factors Sox4 and Sox11 commonly play important roles in the neuronal differentiation of NSCs ( Figure 2) (Andersen et al, 2014;Beckervordersandforth et al, 2010;Codega et al, 2014;Götz et al, 2016;Hsieh, 2012;Liu et al, 2008;Qu et al, 2010).…”
Section: Similarities and Differences Between Neurogenesis And Nscsmentioning
confidence: 99%
“…Indeed, while defined metabolic states are associated with stemness, a switch in metabolic pathways supports divergent cell fate through coordination with signaling and genetic/epigenetic regulation (Folmes et al, 2012b; Shyh-Chang et al, 2013a; Zhang et al, 2012). In the developing brain, a tight balance between self-renewal and differentiation of neural stem cells (NSC) is important to ensure that correct numbers of neural cells are generated (Götz et al, 2016; Urbán and Guillemot, 2014). While several studies have highlighted an important role for glycolysis, lipogenesis and mitochondrial activity in neurogenesis (Knobloch and Jessberger, 2017), the one-carbon (1C) pathway has comparatively received less attention.…”
Section: Introductionmentioning
confidence: 99%